(untitled) (Bangladesh Journal of Medical Science, 2025)
Objective Coronavirus is a new type of virus that causes COVID-19 where the disease causes a fatal impact on sufferers. This study aimed to explore risk factors against the severity of COVID-19, i.e. dyspnea, cough, fever, diarrhea, history of diabetes, hypertension, Chronic Obstructive Pulmonary Disease (COPD), impaired liver function, and Cardiovascular Disease (CVD). Materials and Methods: The author conducted a study search on Friday, March 27th, 2020 at 07.00 – 08.30 PM through the PubMed website. The study search strategy uses the keywords of “COVID-19” or “corona virus”, “symptoms”, “clinical”, “severe”, and other words related to COVID-19. Studies used for meta-analysis must meet inclusion and exclusion criteria. Results and Discussion: Meta-analysis results for significant risk factors include: dyspnea (OR=3.53, 95% CI: 2.62-4.75), diarrhea (OR=1.73, 95% CI: 1.03-2.89), history of diabetes (OR=2.65, 95% CI: 1.77-3.98), hypertension (OR=2.25, 95% CI: 1.64- 3.08), COPD (OR=6.26, 95% CI: 2.47-15.87), and CVD (OR=2.84, 95% CI: 1.64-4.90). Conclusion Patients who have dypsnee and diarrhea symptoms have higher riks of falling into severy COVID. Risk factors for cough symptoms, fever symptoms, and history of impaired liver function are not related to the severity of COVID-19. Patients with comorbidity such as diabetes, hypertension, COPD dan CVD have higher risk to get severe COVID-19. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 202-214